2008
DOI: 10.1073/pnas.0800420105
|View full text |Cite
|
Sign up to set email alerts
|

Cis- andtrans-splicing of mRNAs mediated by tRNA sequences in eukaryotic cells

Abstract: The formation of chimeric mRNAs is a strategy used by human cells to increase the complexity of their proteome, as revealed by the ENCODE project. Here, we use Saccharomyces cerevisiae to show a way by which trans-spliced mRNAs can be generated. We demonstrate that a pretRNA inserted into a premRNA context directs the splicing reaction precisely to the sites of the tRNA intron. A suppressor pretRNA gene was inserted, in cis, into the sequence encoding the third cytoplasmic loop of the Ste2 or Ste3 G proteincou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Importantly, in archaea there is also a precedent for trans-splicing of tRNA halves (19). Thus, the two key requirements for pre-mRNA splicing in trans by the tRNA-splicing machinery, proven in principle by Di Segni et al (5), have already been observed in nature.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Importantly, in archaea there is also a precedent for trans-splicing of tRNA halves (19). Thus, the two key requirements for pre-mRNA splicing in trans by the tRNA-splicing machinery, proven in principle by Di Segni et al (5), have already been observed in nature.…”
mentioning
confidence: 81%
“…In this issue, Di Segni et al (5) designed an elegant system to ask whether tRNAs can be used to recruit the endogenous tRNA-splicing machinery in yeast to mediate mRNA splicing (5). The authors engineered constructs that would produce hybrid pre-tRNA/pre-mRNAs.…”
mentioning
confidence: 99%
“…We used the strain DDS2 (ref. 6), in which the endogenous STE2 gene, as well as the STE3 gene, were previously deleted. Moreover, this strain is devoid of the FAR1 gene, responsible for growth arrest; DDS2, consequently, is able to grow even when the mating pathway is autocrinally activated.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent example of the flexibility of tRNA processing machinery is the demonstration in yeast that a designed STE2 mRNA containing an embedded introncontaining pre-tRNA can be spliced by the tRNA splicing machinery and RNase P to yield both a functional Ste2 protein and a functional tRNA (Di Segni et al 2008).…”
Section: Baroque Trna Gene Organization and Trna Processingmentioning
confidence: 99%